The expressive potential in a dramatic text - Podbevšek, Katarina (Linguistica (Ljubljana), 2017)
The article discusses the linguistic shaping of a dramatic text and its influence on the text's stage speech realisation, using the Slovenian translation of Brecht's one-act play Malomeščanska svatba as an example. A dramatic text typically has a specific - and also graphically visible - textual and linguistic structure that indicates its speech intention. A linguistic analysis of Brecht's text reveals a great expressive potential, both in the stage directions (especially the stage directions for pauses, silence, spoken execution) and in the dialogue (characteristic linguistic elements for spontaneous speech). A short comparison of the text with the stage speech performance shows that the actor used not only prosody (especially pauses) to semantically enrich and rhythmically organise the written language, but also linguistic interventions into the lexical and syntactic structure (repetition, addition, omission, etc.). The great expressive potential of the text thus stimulated the actor's speech and interpretive creativity.
Keywords: "Die Kleinbürgerhochzeit; Brecht, Bertold, 1898-1956; didaskalije; dramska besedila; gledališki govor; igralski govor; Malomeščanska svatba; odrski govor